1992
DOI: 10.1068/p210449
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Gating Effects on Judged Motion of Gratings in Apertures

Abstract: Wallach has described in qualitative terms the movement of lines behind apertures. We related the data he obtained to the aperture problem, constructed a model of movement perception, and carried out tests of the model. Experiment 1 was a parametric study, and showed the conditions under which a reliable illusion (the barber pole illusion) of diagonal movement of lines along an aperture could be obtained, and when fluctuating judgements or veridical percepts were obtained. On the basis of this study a dipole m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
2
13
2
Order By: Relevance
“…Occlusion cues reduce the effect of terminators, as found previously for other depth cues (Shimojo et al, 1989;Stoner et al, 1990;Duncan et al, 2000), and the effect of terminators seems to be quite local in visual space (Power and Moulden, 1992;Kooi, 1993). However, the magnitude of the effects seen for perception is substantially larger than that seen in our population of MT cells.…”
Section: Integration Of Motion Cues In Perception and Behaviorcontrasting
confidence: 51%
See 1 more Smart Citation
“…Occlusion cues reduce the effect of terminators, as found previously for other depth cues (Shimojo et al, 1989;Stoner et al, 1990;Duncan et al, 2000), and the effect of terminators seems to be quite local in visual space (Power and Moulden, 1992;Kooi, 1993). However, the magnitude of the effects seen for perception is substantially larger than that seen in our population of MT cells.…”
Section: Integration Of Motion Cues In Perception and Behaviorcontrasting
confidence: 51%
“…8a). In this case, the barber pole illusion is abolished, and observers perceive the grating to be moving perpendicular to its orientation (Power and Moulden, 1992;Kooi, 1993).…”
Section: Effect Of Aperture Shapementioning
confidence: 98%
“…Lorenceau & Shiffrar, 1992;Shiffrar et al, 1995). Psychophysical studies of the "barber pole" illusion indeed suggest that local 1D and 2D motion signals compete to drive the motion direction perception (Power & Moulden, 1992;Kooi, 1993;Castet et al, 1999). In that sense, the "barber pole" illusion is a powerful tool to investigate surface motion processing.…”
Section: Early and Late Components Of Tracking Initiationmentioning
confidence: 99%
“…Shimojo et al, 1989;Shiffrar et al, 1995;Castet et al, 1999). In understanding how grating and terminator motion signals are integrated, one important step is to tease apart the respective roles of low-level mechanisms, such as spatial interactions between different local motion signals (Power & Moulden, 1992) and higher-level mechanisms, such as occlusion rules or depth perception (Nakayama & Silverman, 1988;Shimojo et al, 1989;Anderson & Sinhia, 1997;Castet et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The exact combinations of grating frequency and speed will produce differences in apparent movement. However, Power and Moulden (1992) have reported that during a 1 min observation period the motion was judged to be along an aperture when the aperture was 1 deg or less in width and 8 deg in length. At 4 deg in width the motion became more ambiguous, with motion along the aperture being reported about 60% of the time.…”
Section: Introductionmentioning
confidence: 97%